Assessment of intermodal freight transport costs - Prata, J. (2014)
The research reported in this paper is part of the R&D project COST-TRENDs, funded by the Portuguese Foundation for Science and Technology. It presents a strategic assessment study of the hinterland connections centred in the Port of Sines, in Portugal, that integrates the core network corridor of the Trans-European Transport Network (TEN-T) designated as the Atlantic corridor. The study comprised the analysis of trends of maritime freight costs until 2020 and the assessment of alternative intermodal freight transport options to reduce costs along the multimodal transport chains. The options evaluated focused in the Iberian section of the Atlantic corridor and included the combination of maritime-short sea shipping, maritime-rail, maritime-road and, also, rail-air modes. The study estimated several key performance indicators for each option which aim to provide useful inputs to transport policy.